2011
DOI: 10.1097/brs.0b013e3181ef9efc
|View full text |Cite
|
Sign up to set email alerts
|

Male-Female Differences in Scoliosis Research Society-30 Scores in Adolescent Idiopathic Scoliosis

Abstract: Males treated with surgery for AIS report better preoperative self-image, less postoperative pain, and better mental health than females. These differences may be clinically significant. For both males and females, the most beneficial effect of surgery is improved self-image/appearance. Overall, the benefits of surgery for AIS are similar for both sexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 29 publications
4
37
2
1
Order By: Relevance
“…5,11,16 We sought to investigate the association between male sex and poor outcomes in a granular, multicenter database of ASD surgeries. We found no association between sex and perioperative complications and no evidence supporting worse HRQOL outcomes for men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,11,16 We sought to investigate the association between male sex and poor outcomes in a granular, multicenter database of ASD surgeries. We found no association between sex and perioperative complications and no evidence supporting worse HRQOL outcomes for men.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, several studies in the pediatric deformity population have demonstrated that sex does play a role in perioperative outcomes. 11,16,22 These studies found that male adolescent idiopathic scoliosis (AIS) patients had greater preoperative curve magnitude, less preoperative curve flexibility, and less deformity correction than female patients. Male patients also had greater estimated blood loss (EBL), longer operative duration, and higher complication rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This symptom is often related to differential diagnoses, such as spinal tumors, syringomyelia, inflammatory processes or visceral disorders 5 . Although preliminary studies have demonstrated that adolescents with idiopathic scoliosis have more pain complaints than control populations 8,9 , there has been no previous research, to our knowledge, on the influence of disease severity on pain intensity. Thus, the aim of this study was to evaluate the presence and intensity of back pain in AIS patients at different stages of the disease.…”
Section: B Introductionmentioning
confidence: 95%
“…The literature shows that outcomes of treatment are considerably different between girls and boys (12)(13)(14)(15)(16)(17)(18). Furthermore, the sexual differences can influence the extent at which deformity impacts the quality of life and self-image, which is shown by using the Scoliosis Research Society questionnaire (19). To our knowledge, in spite of extensive investigations regarding AIS, there are limited studies comparing the curve pattern and demographics between males and females with AIS (20).…”
Section: Introductionmentioning
confidence: 99%